Optimizing Learning Management in Improving the Quality of Language Learning through the Gesture Method - Diana, Eka; Fatmawati, Putri; Rofiki, Moh. (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine how the optimization of learning management can enhance the quality of language learning through the gesture method at AEC Language Course, Kraksaan, Probolinggo. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving course administrators, instructors, and students. The findings indicate that the implementation of the gesture method, managed through the POAC-based learning management system (Planning, Organizing, Actuating, Controlling), can improve students' language comprehension and boost their confidence in speaking English. Furthermore, the application of Total Quality Management (TQM) in learning quality management ensures that the aspects of input, process, and output are optimally managed, thereby increasing the effectiveness of the gesture method in language learning. These findings affirm that a well-structured learning management strategy plays a crucial role in creating a more interactive and effective learning environment.